The reliability of a subtype-determining questionnaire in efficient benign paroxysmal positional vertigo diagnosis in geriatrics - Wan, Yichen; Li, Yingxuan; Sun, Jianjun (Frontiers in Aging Neuroscience, 2023)
Benign paroxysmal positional vertigo (BPPV), as the most common cause of dizziness, especially for the elder, exposes these patients to the lethal risk of falling. However, diagnosis of BPPV in this population can be more elusive as they present less characteristic symptoms. Whereupon, we explored the application of a subtype-determining questionnaire in BPPV diagnosis among the geriatric population. Patients were assigned into the aware group and unaware group, in the former the technician would test the suspected canal indicated by the questionnaire directly while in the latter she carried out the regular positional test. Diagnostic parameters of the questionnaire were examined. The accuracy, sensitivity, specificity of question 1 to 3 for diagnosing BPPV is 75.8%, 77.6%, 74.7% respectively. Question 4 demonstrates an accuracy of 75.6% in ascertaning BPPV subtype, question 5 shows an accuracy of 75.6% in determining the affected side, question 6 yields an accuracy of 87.5% in distinguishing canalithiasis or cupulolithiasis. Examination time was shorter in the aware group (p < .05). No difference was found between the two groups for treatment time(P=0.153). In conclusion, this subtype-determining questionnaire is practical in daily use and capable of providing instructive information for an efficient diagnosis in geriatric BPPV patients.